2018
DOI: 10.14744/anatoljcardiol.2018.57383
|View full text |Cite
|
Sign up to set email alerts
|

Sustained nicorandil administration reduces infarct size in ST-segment elevation myocardial infarction patients with primary percutaneous coronary intervention

Abstract: Objective: Currently, there is still no effective strategy to diminish the infarct size (IS) in patients with ST-segment elevation myocardial infarction (STEMI). According to a previous animal study, nicorandil treatment is a promising pharmaceutical treatment to limit the infarct area. In this study, we aim to investigate the effects of continual nicorandil administration on the IS and the clinical outcomes in patients with STEMI who underwent primary percutaneous coronary intervention (pPCI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In recent years, elderly STEMI patients have been treated effectively after PCI with either tirofi ban, a nonpeptide antagonist of the platelet glycoprotein (GP) IIb/ IIIa receptor and an inhibitor of platelet aggregation, [13] or nicorandil, a vasodilator. [14] The early use of tirofi ban significantly improves myocardial perfusion after PCI, [15,16] and nicorandil has been shown to substantially diminish infarct size in STEMI patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, elderly STEMI patients have been treated effectively after PCI with either tirofi ban, a nonpeptide antagonist of the platelet glycoprotein (GP) IIb/ IIIa receptor and an inhibitor of platelet aggregation, [13] or nicorandil, a vasodilator. [14] The early use of tirofi ban significantly improves myocardial perfusion after PCI, [15,16] and nicorandil has been shown to substantially diminish infarct size in STEMI patients undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%
“…As previous studies have relatively approved the efficacy of chronic oral nicorandil administration in STEMI patients, we did not continue oral nicorandil administration during hospital stay and after discharge. 12,21,30 So, further large scale multicenter randomized control trials with long-term follow ups are recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators could not find the anti‐arrhythmic effect of nicorandil because patients received nicorandil at discharge but not before PCI. The use of nicorandil prior to and post PCI in patients with AMI decreased the incidence of ventricular arrhythmias [151]. Thus, in summary, most clinical data demonstrated that nicorandil did not exhibit a significant anti‐arrhythmic or proarrhythmic effect in patients with AMI.…”
Section: Katp Channels and Ventricular Arrhythmiasmentioning
confidence: 99%
“…Nicorandil reduced infarct size and prevented reperfusion arrhythmias in patients with AMI and reperfusion therapy [147, 151, 162].…”
Section: Katp Channel Openers Prevent Reperfusion Cardiac Injurymentioning
confidence: 99%
See 1 more Smart Citation